Tamactún-Acalán: interpretación de una hegemonía política maya de los siglos xiv-xvi - Andrés Ciudad Ruiz; Alfonso Lacadena García-Gallo (Journal de la Société des Américanistes)
Tamactún-Acalán: a Mayan hegemonic system, 14th-16th centuries. The anthropological studies that analyze the political-territorial structure of the ancient Maya in Pre-columbian times usually highlight the existence of deep transformations between Classic and Post-classic periods. At the same time, there is no agreement among scholars about whether the ancient Maya were politically organized in decentralized states of segmentary nature, or in regional centralized states. Recently, new interpretations have posited the development of hegemonic states retaining many structural features of the preceding formations, but also exhibiting a territorial organization fastering the subordination of several autonomous territories under a same authority. This essay applies this last interpretation to the understanding of the political-territorial structure of the Mactun of Tamactún-Acalán in the 14th-16th centuries A.D., and tests its validity for other regions of the Maya Lowlands, from the beginning of the Classic period to the arrival of the Spaniards, highlighting the parallelisms with other political systems found in Mesoamerica at the time immediately preceding the Conquest.